Novel mutation in USP26 associated with azoospermia in a Sertoli cell‐only syndrome patient. Issue 7 (15th May 2020) - Arafat, Maram; Zeadna, Atif; Levitas, Eliahu; Har Vardi, Iris; Samueli, Benzion; Shaco‐Levy, Ruth; Dabsan, Salam; Lunenfeld, Eitan; Huleihel, Mahmoud; Parvari, Ruti
Abstract: Background: Ubiquitin‐Specific Peptidase 26 ( USP26 ), located on the X chromosome, encodes a deubiquitinating enzyme expressed mainly in testis, where it regulates protein turnover during spermatogenesis and modulates the ubiquitination levels of the Androgen Receptor (AR), and as a consequence, affects AR signaling. Methods: The patient was thoroughly characterized clinically. He was genetically tested by chromosome analysis and whole exome sequencing (WES). Results: The patient was diagnosed with Sertoli cell‐only syndrome pattern (SCOS). The WES analysis revealed only the variation in USP26 : causing p.P469S in a highly evolutionary conserved amino acid as the possible cause for SCOS . The literature search identified 34 single variations and 14 clusters of variations in USP26 that were associated with male infertility. Only one of the 22 variations and of one cluster of three mutations tested for ubiquitination activity was found as damaging. Only one out of six variations tested for effect on AR function was found as damaging. Thus, the association of USP26 with male fertility was questioned. Conclusions: The finding in our patient and the discussion on the reviewed literature support a possible role for USP26 in male fertility. Abstract : Many mutations in USP26 were reported to be causing azoospermia. However, the role of inactivation of this gene as causing azoospermia has been controversial. We present a novel mutation in a Sertoli cell‐only syndrome patient and critically review the previous reports, supporting the role of functional USP26 for male fertility.